MANTRA DALAM NASKAH MERAPI-MERBABU NOMOR 104 KOLEKSI PERPUSTAKAAN NASIONAL REPUBLIK INDONESIA SUNTINGAN TEKS, TERJEMAHAN DAN FUNGSI - , KARTIKA SARI W ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Merapi-Merbabu Manuscript Number 104 is a manuscript in which some of the text contains mantra. This manuscript is stored at The Indonesian Republic National Library (PNRI) in Jakarta. This research will be published as an edition with a translation of Merapi-Merbabu Manuscript Number 104. The edition used in this publication is diplomatic, in order to bring readers close to its original recitation. The method used for translation is a combination of word for word, literal and free method. This edition of Merapi-Merbabu Manuscripts Number 104 is completed with notes that contain explanation and textual criticism. Since I focused on mantra, I have excluded the primbonand pawukon texts that are found in this manuscript.I only focused on folio 4, 11 and 15. Folio 11, folio 4 and folio 15 are the result ofthe successful rearrangement of the manuscript. This arrangement consist of two mantras: MantraI consists of folio 11, and MantraII consists of folios 4 and 15. The recitation of these mantrasis thought to provide self-protection from Brahma, Wishnu and Shiva